1992
DOI: 10.1164/ajrccm/145.2_pt_1.377
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Output Response to Continuous Positive Airway Pressure in Congestive Heart Failure

Abstract: The effects of nasal continuous positive airway pressure (CPAP) were examined during cardiac catheterization in 22 patients with congestive heart failure (CHF). CPAP was applied at a level of 5 cm H2O pressure. Hemodynamic measurements were made at baseline and while on CPAP. We hypothesized that patients with high left ventricular (LV) diastolic pressures would experience an increase in cardiac index (CI). To test this hypothesis, patients were divided into two groups based on their baseline pulmonary capilla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
206
4
6

Year Published

1995
1995
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 339 publications
(229 citation statements)
references
References 9 publications
13
206
4
6
Order By: Relevance
“…In agreement with other reports [11,14,25,26], the authors found that CPAP is an effective treatment for patients with CSR. This was manifested by significant improvements in the percentage of CSR during sleep, AHI, sleep quality, arousal index, mean circulation time, Epworth sleepiness score and the NYHA class.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In agreement with other reports [11,14,25,26], the authors found that CPAP is an effective treatment for patients with CSR. This was manifested by significant improvements in the percentage of CSR during sleep, AHI, sleep quality, arousal index, mean circulation time, Epworth sleepiness score and the NYHA class.…”
Section: Discussionsupporting
confidence: 92%
“…The fact that ventilatory parameters during sleep were improved in all patients with the same settings suggests that the beneficial effects of positive intrathoracic pressure upon the failing heart are the predominant mechanism of benefit. In various studies, BRADLEY and co-workers [11,26] demonstrated that CPAP is effective not only in improving respiratory events but also in reducing cardiac pre and after load, transmural pressure of intrathoracic blood vessels [32] and cardiac dimensions [33]. The current finding of a reduction in circulation time is also consistent with improved cardiac performance.…”
Section: Discussionsupporting
confidence: 56%
“…Moreover, CPAP decreased the plasma concentrations in atrial and brain natriuretic peptides of indicators of cardiac function, which is consistent with Tkakova and co-workers (17). As long as the dominant apneas/hypopneas in Cheyne-Stokes respiration are central, rather than obstructive, CPAP set at 5 cmH2O can hydrostatically benefit these patients through elevating intra-thoracic pressure and thus lowering left ventricular afterload (18). In summary, the amelioration of sleep quality and cardiac function with CPAP in the genetically diagnosed case of KWD with possible secondary dilated cardiomyopathy have clinical implications, considering the paucity of therapeutic options in most degenerative neuromuscular disorders.…”
Section: Discussionsupporting
confidence: 86%
“…In patients with CHF and LV dysfunction, on the other hand, CO is dependent on postload changes. Thus, a considerable preload increase in the patient with LV dysfunction impairs the cardiac function due to the changes that take place in myocardial tension and length properties, mainly at the left heart chamber 28 .…”
Section: Arq Bras Cardiol 2007; 88(1) : 86-92mentioning
confidence: 99%